2021
DOI: 10.3389/fphar.2021.664836
|View full text |Cite
|
Sign up to set email alerts
|

Notopterol Attenuates Estrogen Deficiency-Induced Osteoporosis via Repressing RANKL Signaling and Reactive Oxygen Species

Abstract: Integrity of the skeleton is sustained through the balanced activities of osteoblasts and osteoclasts in bone remodeling unit. The balance can be disrupted by excessive osteoclasts activation commonly seen in osteoporosis. Notopterol (NOT) is a main component of Notopterygium incisum which exerts a wide spectrum effect on biomedical pharmacology. In our study, we found NOT serves as an inhibitor in regulating RANKL-activated osteoclasts formation and bone resorption function by calculating tartrate resistant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…On the one hand, evidence suggested that various ROS triggers could impair ovarian function and that some antioxidants, such as melatonin and resveratrol, could ameliorate excess ROS-induced damage, indicating that excessive oxidative stress may result in the incidence of POI [ 38 ]. On the other hand, oestrogen deficiency as a result of POI is associated with increased oxidative stress, inducing cardiac dysfunction and osteoporosis [ 39 , 40 ]. To determine the causality between the metabolomics changes and POI, further prospective cohort studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, evidence suggested that various ROS triggers could impair ovarian function and that some antioxidants, such as melatonin and resveratrol, could ameliorate excess ROS-induced damage, indicating that excessive oxidative stress may result in the incidence of POI [ 38 ]. On the other hand, oestrogen deficiency as a result of POI is associated with increased oxidative stress, inducing cardiac dysfunction and osteoporosis [ 39 , 40 ]. To determine the causality between the metabolomics changes and POI, further prospective cohort studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 100-μM Rd inhibited osteoclastogenesis of not only RAW264.7 cells, a mice preosteoclastic cell line, but also mice BMDMs treated with RANKL and M-CSF, as shown by the dramatic reduction in the amount and volume of TRAP(+) osteoclasts. TRAP is an extracellular enzyme encoded by Acp5 gene that is commonly utilized to identify osteoclasts, while metalloproteinase (MMP)-9 is vital in mature osteoclasts to mediate bone resorption ( Gu et al., 2014 ; Chen et al., 2021 ). Nuclear factor of activated T cells (NFAT) c1 is one of the main transcription factors in osteoclastogenesis, which could promote the expression of Acp5 and Mmp9 genes ( Egusa et al., 2011 ; Deng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are beneficial by acting as intracellular signaling factors and detrimental as increasing with age, inflammatory state or age-related diseases ( Go and Jones, 2017 ). Excess ROS destroy bone by reducing the level of antioxidant enzymes and preventing the differentiation of OBs and the formation of OCs ( Chen et al, 2021 ). During the differentiation in osteoclasts, RANKL binds to the receptor RANK, which activates TRAF6 to drive multiple downstream targets.…”
Section: Receptor Activator Of Nuclear Factor-κb Ligand-mediated Clas...mentioning
confidence: 99%